2006
DOI: 10.1111/j.1399-6576.2006.01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of shivering during regional anaesthesia: prophylactic ketamine and granisetron

Abstract: The prophylactic use of 0.5 mg/kg i.v. ketamine was effective in preventing shivering developed during regional anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
105
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(127 citation statements)
references
References 25 publications
10
105
1
2
Order By: Relevance
“…However, in this study, the incidence of shivering was 50% (in control group and at 30 min). In a study by Wason et al [12], the prevalence of shivering was 54% and was similar to that in the study of Sagir et al [17]. Although, Sia et al [18] reported the incidence of shivering as less in their study (40%), it was found in our study that the sensory block occurred with injections.…”
Section: Discussioncontrasting
confidence: 54%
“…However, in this study, the incidence of shivering was 50% (in control group and at 30 min). In a study by Wason et al [12], the prevalence of shivering was 54% and was similar to that in the study of Sagir et al [17]. Although, Sia et al [18] reported the incidence of shivering as less in their study (40%), it was found in our study that the sensory block occurred with injections.…”
Section: Discussioncontrasting
confidence: 54%
“…However, none of our patient had tachycardia (H.R. >100 /min) or hypertension (BP >140 /90), findings of the present study corroborate well with the findings of Sagir O et al 12 In the present study the incidence of hypotension was 16% in midazolam, 7% in ketamine, 13 % in ketamine plus midazolam group. These findings are similar to the study done by Abdelrahman RS on prevention of shivering during regional anaesthesia.…”
Section: Discussionsupporting
confidence: 82%
“…bupivacaine. 12 But this incidence of shivering was reduced to zero in ketamine group in his study. While the present study shows 33% incidence in Ketamine group.…”
Section: Discussionmentioning
confidence: 99%
“…Dal et al and Sagir et al reported that ketamine 0.5mg/kg prevented effectively postanesthetic shivering in patients receiving general anesthesia and spinal anesthesia respectively. 23,24 Whereas we used 0.25mg/kg of ketamine in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Its dosage to control shivering is usually 0.25-0.75mg/kg intravenously, with side effects like drowsiness, delirium, hallucination. 8 Dexmedetomidine acts as antishivering agent by means it being a α-2-adrenergic receptor agonist with potent effects on the central nervous system. 9 We carried out this study to compare between an intravenous low dose of ketamine and an intravenous infusion of dexmedetomidine for prevention of intraoperative shivering during spinal anesthesia.…”
Section: Introductionmentioning
confidence: 99%